Findings and Recommendations for Decision-makers - Barugahara, Ismail; Cherry, Andy; Haffner, Stefan A.; Haselip, James A.; Mailula, Cheka; Musolino, Najia (CAAST-Net Plus, 2015)
This publication contains the findings and recommendations for decisionmakers that emerged from discussion at the 1st CAAST-Net Plus Stakeholder Forum. The forum convened 60 African and European experts working across three global challenge areas of special interest for CAAST-Net Plus: food and nutrition security, climate change, and health. The findings and recommendations presented here focus on the development of crosscutting support mechanisms, frameworks and viable policy options for using science, technology and innovation (STI) to tackle these global challenges.